Une méthode pour approcher les présentations de soi dans les communications : l’analyse des adresses - Martine Dutoit (Éducation et Socialisation)
A large number of researches, with something other than the self-presentation, in particular researches in education and training, use of material fact as information obtained under conditions of self-presentation, which immediately raises the question of the influence of this communication statements collected by the researcher. Often, he believes has accesed to a personal and private speech, then it is a word addressed. It’s difficult in these conditions to don’t report the contents of the speech and the addressing of the speech prior to use for research. The purpose of this article is to present and explore a methodological approach and its results for the analysis of self-presentation as a group in a communication situation. The baseline scenario is a situation of public communication of people labeled (psychiatric patients) aimed at changing representations of the recipients on their group affiliation. It was chosen, in particular, to focus the analysis of « addresses» speech.